Diabetic Foot: Surgical Approach in Emergency. (23rd October 2013) - Setacci, C.; Sirignano, P.; Mazzitelli, G.; Setacci, F.; Messina, G.; Galzerano, G.; de Donato, G.
Abstract : Introduction . Critical limb lschemia (CLI) and particularly diabetic foot (DF) are still considered "Cinderella" in our departments. Anyway, the presence of arterial obstructive disease increases the risk of amputation by itself; when it is associated with foot infection, the risk of amputation is greatly increased. Methods . From January 2007 to December 2011, 375 patients with DF infection and CLI have been admitted to our Unit; from 2007 to 2009, 192 patients (Group A) underwent surgical debridement of the lesion followed by a delayed revascularization; from 2010 to 2011, 183 patients (Group B) were treated following a new 4-step protocol: (1) early diagnosis with a 24 h on call DF team; (2) urgent treatment of severe foot infection with an aggressive surgical debridement; (3) early revascularization within 24 hours; (4) definitive treatment: wound healing, reconstructive surgery, and orthesis. We reported rates of mortality, major amputation, and foot healing at 6 months of followup. Results . The majority of patients in both groups were male; no statistical differences in medical history and clinical condition were reported at the baseline. The main difference between the two groups was the mean time from debridement to revascularization (3 days in Group A and 24 hours in Group B). After 6 months of follow-up, mortality was 11% in Group A versus 4.4% in Group B. Major amputation rate was 39.6% and 24.6% in Groups A and B, respectively. Wound healing was achieved in 17.8% in Group A and 20.8% in Group B. Conclusions . This protocol requires a lot of professional skills that should to reach the goal to avoid major amputations in patients with DF. Only an interdisciplinary integrated DF team and an early intervention may significantly impact the outcome of our patients: "Time is Tissue"!